Application of Deep Learning-Based Tolerance Values to Support Classroom Management in Class VI SDN Beji 01 Ungaran Timur - Reva Adelya Wulan Dari; Nur Aini Pusvitasari; Aulia Nur Laila; Nimas Puspitasari (Proceeding of the International Conference on Global Education and Learning, 2025)
This study aims to describe the application of deep learning based tolerance values with a pedagogical approach in supporting classroom management in grade VI of SDN Beji 01 East Ungaran. The deep learning approach is understood as a pedagogical strategy that emphasizes the cognitive, affective, and social engagement of students through meaningful learning experiences. This study uses a descriptive qualitative approach with data collection techniques in the form of semi-structured interviews, observations, and documentation. The research subjects include grade VI teachers, principals, and students with diverse social and cultural backgrounds. The results of the study show that the application of tolerance values through deep learning strategies is able to create an inclusive, safe, and conducive classroom climate. The implementation is reflected through the practice of random seating arrangements, a culture of sharing learning media, deliberation in conflict resolution, fair study timing, and strengthening mutual respect between students. These findings confirm that the integration of deep learning-based tolerance values contributes significantly to the effectiveness of classroom management and the strengthening of the social character of elementary school students.